Vol 15 No 1 (2021) Tata Kelola Manajemen Kepala Desa dan Implikasi UU No. 6 Tahun 2014: Studi Kasus Desa Sukaharja Kecamatan Cijeruk Kabupaten Bogor - Achmad Jaelani Achmad Jaelani (LPPM Swadaya Institute of Business and Communication, 2021)
The political contestation in Sukaharja Village, District Cijeruk, Bogor Regency, West Java is interesting to research The fight for the position of village chief in the village is dominated by the two strongholds. Those are stronghold of Mr. Tatang and stronghold of Mr. Santoso. The process of village elections (Pilkades) was unfair and gave benefit for certain stronghold. When they served, either in the reign of Mr. Tatang and in the present government (Mr. Santoso), both of them practice nepotism by appointing RT and RW from relatives / family. The community lets the practice of nepotism occurs for the reasons like they can still live comfortably and prosperously despite the fact that it only be a time bomb and will be a negative impact for the communities themselves at a later date. The enactment of UU No. 6 tahun 2014 became the hope that the practice of nepotism that has entrenched can be prevented and minimized.